Coupling far and near tectonic signals in syn-orogenic sediments: the Olvena growth strata (Sierras Marginales, southern Pyrenees) - P. SANTOLARIA; A. LUZÓN; A.M. CASAS; R. SOTO (Geologica Acta, 2015)
The Olvena area (Sierras Marginales, southern Pyrenees) provides an outstanding example for studying the relationships between tectonics and sedimentation related to fold-and-thrust systems having shallow décollements. Stratigraphic and sedimentological features allow infer i) the relationship between Oligocene-Miocene locallysourced alluvial fans and a far-sourced wider fluvial system, and ii) the control exerted by tectonics on the stratigraphic architecture. Initially, uplift resulting from folding and thrusting in the Sierras Marginales precluded the entrance through this area into the Ebro basin of a wide fluvial system sourced in internal zones of the Pyrenean chain (including the Axial Zone). A subsiding area was created in the southern front of the Sierras where west-flowing alluvial fans generated, having their source areas in the rejuvenated reliefs. The subsequent cessation of movement of the tectonic structures permitted these reliefs to be subdued and the overpassing of the north-coming fluvial system that progressively covered a wider area. Sequential evolution and stratigraphic architecture evidence thrust emplacement geometry and chronology, including out-of-sequence reactivation of structures and the influence of evaporite flow along the décollement. Although these syn-tectonic deposits belong to the Ebro basin succession, its megasequential evolution differs from the general sequence established for the basin fill, highlighting the importance of differentiating the influence of near-coming sedimentary systems when interpreting basin-scale sequence stratigraphy.